Longitudinal x-ray based lung function measurement for monitoring Nintedanib treatment response in a mouse model of lung fibrosis - Khan, Amara; Markus, M. Andrea; Svetlove, Angelika; Hülsmann, Swen; Alves, Frauke; Dullin, Christian (Scientific reports, 2023)
Lung fibrosis (LF) is a chronic progressive, incurable, and debilitating condition of the lung, which is associated with different lung disease. Treatment options are still sparse. Nintedanib, an oral tyrosine kinase inhibitor, significantly slows the LF progression. However, there is a strong need of further research and the development of novel therapies. In this study, we used a correlative set-up that combines X-ray based lung function (XLF) with microCT and whole body plethysmography (WBP) for a comprehensive functional and structural evaluation of lung fibrosis (LF) as well as for monitoring response to orally administered Nintedanib in the mouse model of bleomycin induced LF. The decline in lung function as early as one week after intratracheal bleomycin instillation was reliably detected by XLF, revealing the lowest decay rate in the LF mice compared to healthy ones. Simultaneously performed microCT and WBP measurements corroborated XLF findings by exhibiting reduced lung volume V insp μCT and tidal volume TV WBP. In LF mice XLF also revealed profound improvement in lung function one week after Nintedanib treatment. This positive response to Nintedanib therapy was further substantiated by microCT and WBP measurements which also showed significantly improved Vinsp mu CT and TV WBP in the Nintedanib treated mice. By comparing the XLF data to structural features assessing the extent of fibrosis obtained by ex-vivo high-resolution synchrotron radiation-based imaging and classical histology we demonstrate that: (1) a simple low dose x-ray measurement like XLF is sensitive enough to pick up treatment response, (2) Nintedanib treatment successfully improved lung function in a bleomycin induced LF mouse model and (3) differences between the fully restored lung function and the partially reduced fibrotic burden compared to healthy and untreated mice. The presented analysis pipeline underlines the importance of a combined functional and anatomical readout to reliably measure treatment response and could easily be adapted to other preclinical lung disease models.
Gesehen am 22.01.2024